(5a-8b) + 3(-a + 2b)
tolong dibantu yahhh
tolong dibantu yahhh
Penjelasan dengan langkah-langkah:
____________________________
(5a - 8b) + 3(-a + 2b)
= 5a - 8b - 3a + 6b
= (5a - 3a) + (- 8b + 6b)
= 2a + (-2b)
= 2a - 2b
[answer.2.content]Electric Scooter for Kids Salt Lake City Utah
Electric Scooter for Kids Salt Lake City Utah
Penjelasan dengan langkah-langkah:
____________________________
(5a - 8b) + 3(-a + 2b)
= 5a - 8b - 3a + 6b
= (5a - 3a) + (- 8b + 6b)
= 2a + (-2b)
= 2a - 2b
[answer.2.content]